Applicability of kenaf-based hybrid composite for aircraft radome - Mohd Haris, Mohd Yusoff (2014)
In this research, the potential of natural fibre is explored for use in aircraft radome application. An aircraft radome usually refer to radar transparent, dome-shape structure which protects radar antennas on aircraft from aerodynamic loading, weather, as well as impacts from bird strikes. Materials that are used for small aircraft radome usually have low dielectric constant and high toughness. However, the need for biodegradable materials has prompted the usage of natural fibres. Natural fibres have comparable mechanical properties such as low weight, low cost, and are renewable and biodegradable. Based on previous research conducted, kenaf fibre has been used for car bumper due to impact property and antenna due to low dielectric property. To date, there are no applications of hybrid kenaf composite in aircraft parts, where it is approved according to the airworthiness standard by Federal Aviation Regulation has been reported. Therefore, this research will provide a motivation to explore a new potential application and particular on the aerospace industry. To assess the potential of natural fibre composite for aircraft radome application, a solid laminate hybrid composite radome design composed of kenaf fibre and fibreglass with epoxy resin is proposed. To fabricate the radome structure, a closed mould vacuum infusion manufacturing process is developed and optimized in order to produce radome structure with consistent wall thickness. Current fabrication technique employed the more traditional hand lay-up technique. Radome structure based on a Duke 60 Beechcraft is fabricated using hybrid of kenaf/fibreglass with epoxy as solid laminates. Current aircraft radome used fibreglass epoxy laminates is also fabricated as the control configuration. Effect of silane chemical treatment on the kenaf fibre was also investigated and denoted as hybrid composite treated kenaf. The physical, mechanical and microstructure of all configurations were later assessed and comparisons are made. Experimental investigations were also carried out to assess the energy absorption capability and load carrying capacity of all configurations subjected to quasi-static axial compressive load. Six test are conducted to analysed performance of hybrid composite for aircraft radome which is i) water absorption test, ii) density test, iii) dielectric constant test, iv) tensile test, v) quasi static test and vi) scanning electron microscope (SEM). The summary of result for each type of result is stated below. For water absorption, hybrid composite untreated kenaf is 5.73%, hybrid composite treated kenaf is 4.53% and fibreglass composite is 0.86%. For density test, hybrid composite untreated kenaf is 1383 kg/m3 , hybrid composite treated kenaf is 1440 kg/m3 and fibreglass composite is 1877 kg/m3 . For dielectric constant test, hybrid composite untreated kenaf is 2.97, hybrid composite treated kenaf is 1.28 and fibreglass composite is 3.52. For ultimate tensile test, hybrid composite untreated kenaf is 32.54 MPa, hybrid composite treated kenaf is 38.25 MPa and fibreglass composite is 89.92 MPa. For quasi static test, energy absorb by hybrid composite untreated kenaf is 1534Nm, hybrid composite treated kenaf is 1708 Nm and fibreglass composite is 3910Nm. By using this result and additional two more criteria added which is cost and renewable, the technique for order preference by similarity to ideal solution or TOPSIS is used to determine best alternative material as closed as ideal possible to ideal solution based on three types of composite configuration. Fabrication the aircraft radome part by using closed mould system via vacuum infusion process is successful given a consistency thickness. From TOPSIS analysis on rank alternative material, hybrid composite treated kenaf is near to ideal solution comparing to hybrid composite untreated kenaf and fibreglass composite.